Occurrence of autoantibodies against skin proteins in patients with hereditary epidermolysis bullosa predisposes to development of autoimmune blistering disease - Lehr, Saskia; Felber, Felicitas; Tantcheva-Poór, Iliana; Keßler, Christina; Eming, Rüdiger; Nyström, Alexander; Rizzi, Marta; Kiritsi, Dimitra (Frontiers in Immunology, 2022)
Skin blistering disorders are associated with inherited defects in proteins involved in the dermal-epidermal adhesion or autoantibodies targeting those proteins. Although blistering in hereditary epidermolysis bullosa (EB) is pathogenetically linked to genetic deficiency of distinct proteins of the epidermis or the dermal-epidermal junction, circulating autoantibodies against these proteins have also been identified in EB patients. So far, autoantibodies have been considered bystanders in EB and active pathogenicity of them in EB has not been disclosed. In sera of a cohort of 258 EB patients, we found by ELISA in 22 % of the patients autoantibodies against the bullous pemphigoid antigen BP180. The titers correlated negatively with collagen VII skin expression and disease severity. Among those patients, we identified six (2.33 %) with clinical features of an autoimmune bullous disorder (AIBD) and positive indirect immunofluorescence (IIF) staining. In literature, we found four more cases of EB patients developing disease-aggravating AIBD. Co-existence of these two rare skin disorders suggests that EB patients have a predisposition for the development of AIBD. Our work highlights that EB patients with increased itch or blister formation should be evaluated for additional AIBD and repeated screening for changes in autoantibody titers and skin-binding specificities is advised.